2020
DOI: 10.3389/fpsyt.2020.577491
|View full text |Cite
|
Sign up to set email alerts
|

Trait Disinhibition and NoGo Event-Related Potentials in Violent Mentally Disordered Offenders and Healthy Controls

Abstract: Trait disinhibition may function as a dispositional liability toward maladaptive behaviors relevant in the treatment of mentally disordered offenders (MDOs). Reduced amplitude and prolonged latency of the NoGo N2 and P3 event-related potentials have emerged as promising candidates for transdiagnostic, biobehavioral markers of trait disinhibition, yet no study has specifically investigated these two components in violent, inpatient MDOs. Here, we examined self-reported trait disinhibition, experimentally assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…There is evidence that childhood trauma and different forms of early neglect could cause neurobiological effects that may obstruct the brain’s ability to control and regulate emotions, which might make these individuals more susceptible to impulsivity [ 41 ]. This could be especially important to investigate in groups such as forensic psychiatric patients who have complex comorbidities and impulsive behaviours, since initial findings report disinhibition to be associated with reduced neural efficiency during later outcome monitoring or behaviour evaluations [ 42 ]. Furthermore, an extensive review concluded that psychological, emotional, social, behavioural, and academic problems in childhood were more common among individuals who had witnessed interparental violence than in those who had not.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that childhood trauma and different forms of early neglect could cause neurobiological effects that may obstruct the brain’s ability to control and regulate emotions, which might make these individuals more susceptible to impulsivity [ 41 ]. This could be especially important to investigate in groups such as forensic psychiatric patients who have complex comorbidities and impulsive behaviours, since initial findings report disinhibition to be associated with reduced neural efficiency during later outcome monitoring or behaviour evaluations [ 42 ]. Furthermore, an extensive review concluded that psychological, emotional, social, behavioural, and academic problems in childhood were more common among individuals who had witnessed interparental violence than in those who had not.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more interesting result is related to the significant correlation between benign online disinhibition and ITPV perpetration (and not victimization) in the overall sample. The general effect of disinhibition may explain this specific result within maladaptive behaviors (Kyranides et al, 2017 ) and disinhibition as a psychological trait (i.e., “a dispositional liability toward maladaptive behaviors”; Delfin et al, 2020 ) and not necessarily related to one’s online behavior (toxic or benign). However, to test these assumptions, future, more complex related investigations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that a subsample of this current group of forensic psychiatric patients (male participants with a violent history) showed more disinhibitory behaviors than controls. Their higher level of disinhibition was associated with slower response and slower neural information processing during a response inhibition task, suggesting less efficient neural information processing in these patients ( Delfin et al, 2020 ). Although the current results cannot corroborate this suggestion, they do indicate that the ability to refrain from impulsive behaviors is especially reduced in forensic psychiatric patients who self-harm.…”
Section: Discussionmentioning
confidence: 99%